Analisis Pengaruh Faktor Internal dan Faktor Ekternal terhadap Kinerja Reksa Dana Syariah Saham - Fathimah Awliyaul Alim; Muhamad Umar Mai; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2021)
This research aims to find out what things can affect the performance of Islamic equity funds. Four independent variables were taken based on research released and classified as internal factors (Stock Selection, Mutual Fund Age) and external factors (Jakarta Islamic Index and Inflation Rate) to initiate the relationships in the performace of sharia equity funds as the dependen variables. The performance of Islamic equity funds use the Sharpe method and calculated for 36 months from January 2017 to December 2019. Research data taken from secondary data published by Bareksa, Jakarta Islamic Index and Bank Indonesia. Research method uses quantitative-descriptive in path analysis model. The result shows that Stock Selection, Mutual Fund Age, and Jakarta Islamic Index significantly influence the performace of sharia equity funds. Meanwhile the Inflation Rate doesn’t significantly influence the performace of sharia equity funds.